Sostoyaniye kletochnykh i gumoralnykh faktorov immuniteta lyzhikov-gonshchikov na razlichnykh etapakh trenirovochnogo tsikla - Fomin, N. A.; Rybakov, V. V.; Kulikov, L. M. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this study was to reveal the changes of cellular and humoral factors of immunity at various stages of the year training cycle. 193 cross-country skiers of national and international level aged from 17 to 26 acted as the subjects of this research. Immunological, physiological and biochemical monitoring was held during one year. As a result of the research it had been stated that the high reactivity of the elite cross-country skiers at the stage of the main starts changes into respectively stable indicies of cellular and humoral immunity. Theathletes of the national level do not demonstrate such changes at the stage of the main starts. The positive correlation had been revealed in the dynamics of humoral and cellular factors of immunity and the changes of the protein fractions of blood, the peroxidation of lipids and the activity of the blood antioxidant system.